Pengaruh Viral Marketing, Experiential marketing Dan Persepsi Harga Terhadap Minat Beli Ulang produk Mixue Ice Cream & Tea Pada gen Z - Agustinus Herinama, Agustinus; Setiawan, Yuli (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
This study aims to determine the effect of viral marketing, experiential marketing, and price perceptions on repurchase interest in mixue ice cream & tea products in Gen Z, both simultaneously and partially. This research design uses quantitative methods with non-probability sampling techniques. The population of this study is Generation Z, which has consumed Mixue at the Gandaria City branch. A sample of 80 respondents used the Roscoe formula. The data analysis method used is multiple linear regression analysis, F test (simultaneous), t-test (partial), and Coefficient of Determination (Adjusted R Square) with the help of SPSS 25 software. This study's results indicate a simultaneous influence between the variables Viral Marketing, Experiential Marketing, and Price Perception on Repurchase Interest. Partially, Viral Marketing and Experiential Marketing have a positive effect on Repurchase Interest. Meanwhile, Price Perception hurts Repurchase Interest. Keywords : viral marketing, experiential marketing, price perception, on repurchase interest.